An Old Testament theology : an exegetical, canonical, and thematic approach - Waltke, Bruce K.; Yu, Charles (Grand Rapids, MI Zondervan, 2007)
The Old Testament is more than a religious history of the nation of Israel. It is more than a portrait gallery of heroes of the faith. It is even more than a theological and prophetic backdrop to the New Testament. Beyond these, the Old Testament is inspired revelation of the very nature, character, and works of God. As renowned Old Testament scholar Bruce Waltke writes in the preface of this book, the Old Testaments every sentence is fraught with theology, worthy of reflection. This book is the result of decades of reflection informed by an extensive knowledge of the Hebrew language, the best of critical scholarship, a deep understanding of both the content and spirit of the Old Testament, and a thoroughly evangelical conviction. Taking a narrative, chronological approach to the text, Waltke employs rhetorical criticism to illuminate the theologies of the biblical narrators. Through careful study, he shows that the unifying theme of the Old Testament is the breaking in of the kingdom of God. This theme helps the reader better understand not only the Old Testament, but also the New Testament, the continuity of the entire Bible, and ultimately, God himself. - Publisher.
The basis of Old Testament theology -- The task of Old Testament theology -- The method of biblical theology, part 1; hermeneutica sacra -- The method of biblical theology, part 2: narrative theology -- The method of biblical theology, part 3: poetics and intertextuality -- The Bible's center: an overview of an Old Testament theology -- The gift of the cosmos -- The gift of Adam -- The gift of the bride -- The gift of the garden; humanity on probation and the fall -- The gift of the Noahic covenant -- The gift of the Abrahamic covenant: the chosen seed --
Includes bibliographical references (pages 970-990) and indexes.
Keywords: Bible. -- Theology